Prenatal diagnosis of vein of Galen malformation; antenatal ultrasound aiding prognosis and postnatal management - Lodha, Pooja; Sharma, Rajiv; Kaul, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We present a case of Vein of Galen Malformation (VGAM) diagnosed prenatally with 3 dimensional color and power Doppler ultrasonography. On the basis of prenatal imaging, the arterial feeders, drainage and secondary damage like hydrocephalus and cerebral thinning were assessed. This can be useful in counseling patients and providing a realistic view of outcome and management after birth. This is of utmost importance in a country like India, where there is disparity in services and infrastructure in maternity hospitals.